A phase II trial evaluating the feasibility of adding bevacizumab to standard osteosarcoma therapy. Issue 7 (3rd July 2017) - Navid, Fariba; Santana, Victor M.; Neel, Michael; McCarville, M. Beth; Shulkin, Barry L.; Wu, Jianrong; Billups, Catherine A.; Mao, Shenghua; Daryani, Vinay M.; Stewart, Clinton F.; Kunkel, Michelle; Smith, Wendene; et al.
Abstract : Increased vascular endothelial growth factor (VEGF) expression in osteosarcoma correlates with a poor outcome. We conducted a phase II trial to evaluate the feasibility and efficacy of combining bevacizumab, a monoclonal antibody against VEGF, with methotrexate, doxorubicin and cisplatin (MAP) in patients with localized osteosarcoma. Eligible patients received two courses of MAP chemotherapy before definitive surgery at week 10. Bevacizumab (15 mg/kg) was administered 3 days before starting chemotherapy then on day 1 of weeks 3 and 5 of chemotherapy. After surgery, patients received MAP for a total of 29 weeks; bevacizumab was added every 2 or 3 weeks on day 1 of chemotherapy at least 5 weeks after surgery. Group sequential monitoring rules were used to monitor for unacceptable bevacizumab‐related targeted toxicity (grade 4 hypertension, proteinuria or bleeding, grade 3 or 4 thrombosis/embolism, and grade 2–4 major wound complications). Thirty‐one patients (median age 12.8 years) with localized osteosarcoma were enrolled. No unacceptable targeted toxicities were observed except for wound complications (9 minor and 6 major), which occurred in 15 patients; none required removal of prosthetic hardware or amputation. The estimated 4‐year event‐free survival (EFS) rate and overall survival rate were 57.5 ± 10.0% and 83.4 ± 7.8%, respectively. Eight (28%) of 29 evaluable patients had good histologic response (<5% viable tumor) to preoperative chemotherapy. The addition of bevacizumab to MAP for localized osteosarcoma is feasible but frequent wound complications are encountered. The observed histologic response and EFS do not support further evaluation of bevacizumab in osteosarcoma. Abstract : What's new? Increased expression of vascular endothelial growth factor (VEGF) is associated with a poor prognosis in patients with osteosarcoma. In this study, the authors asked whether the anti‐VEGF drug bevacizumab might enhance standard chemotherapy and improve patient outcomes. Unfortunately, despite promising preclinical studies, the answer was no. The bevacizumab also increased the risk of serious wound‐healing complications. The authors conclude that further evaluation of bevacizumab in osteosarcoma is therefore not warranted. However, the study provides important data regarding the use of antiangiogenic agents when surgical resection of a primary bone tumor is required.